MODERN PROSPECTS FOR THE DIAGNOSIS AND TREATMENT OF ACUTE RHEUMATIC FEVER - Kuldashev Sardor Furqatovich; Normakhmatov Bakhtiyor Botiralievich; Makhammatov Azamat Alikulovich (Scholar Express Journals, 2023)
The description of gender equality as the value of law in discourse of anthropological tendency is given in the article. Considered right to differences in the aspect of gender mainstreaming in law. The main components of gender equality are characterized. Despite significant progress in reducing the incidence, acute rheumatic fever (ARF) has been observed in all countries of the world over the past decades. Determining the features of the course of the disease is important for timely diagnosis, which requires a thorough analysis of clinical, laboratory and instrumental data
Keywords: diagnosis; observed; gender; laboratory